High-wear-resistance polyurethane wheel and manufacturing process thereof
By combining polymer polyurethane with nano-scale reinforced fibers to form a highly crosslinked three-dimensional network structure, the problems of poor wear resistance, tear strength and aging resistance of polyurethane wheels are solved, and performance improvement and application expansion are achieved.
Patent Information
- Application Number
- CN202411554190.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-04
- Publication Date
- 2025-02-28
AI Technical Summary
Existing polyurethane wheels have poor performance in wear resistance, tear strength and aging resistance, limiting their application in demanding industrial fields.
By combining polymer polyurethane with nano-scale reinforced fibers, a highly crosslinked three-dimensional network structure is formed, which improves the wear resistance, tear strength and aging resistance of the wheel.
The comprehensive performance improvement of polyurethane wheel has been achieved and its application prospects in various industrial fields have been enhanced.
Smart Images

Figure CN119529507A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of polymer materials, in particular to a high-wear-resistant polyurethane wheel and a manufacturing process thereof. Background Art
[0002] Polyurethane wheels, with their unique material properties and wide application fields, have brought great convenience to modern industrial production and daily life. In the prior art, although polyurethane wheels have many advantages, they perform poorly in terms of wear resistance, tear strength and aging resistance. These deficiencies limit their application in certain high-demand industrial fields. In order to overcome these problems, the present invention combines polymer polyurethane with nano-scale reinforcing fibers to form a highly cross-linked three-dimensional network structure, thereby improving the wear resistance, tear strength and aging resistance of the wheel. This innovation not only improves the comprehensive performance of polyurethane wheels, but also expands its application prospects in various industrial fields. Summary of the invention
[0003] 1. Technical issues to be solved
[0004] In view of the deficiencies in the prior art, the present invention provides a highly wear-resistant polyurethane wheel and a manufacturing process thereof, which has the advantages of wear resistance, tear resistance and aging resistance, and solves the problem of poor wear resistance, tear strength and aging resistance of polyurethane wheels in the prior art.
[0005] (II) Technical solution
[0006] To achieve the above-mentioned purpose, the present invention provides the following technical scheme: a highly wear-resistant polyurethane wheel, wherein the formula of the polyurethane wheel consists of basic raw materials, fillers and additives, and the formula raw materials and their mass parts are: 14-18 parts of fluorine-containing polyurethane; 17-20 parts of aliphatic polyurethane elastomer; 5-8 parts of polyvinyl pyrrolidone nanofibers; 9-11 parts of basalt nanofibers; 4-6 parts of polyphenylene sulfide nanofibers; 0.6-0.7 parts of glycerol; 0.22-0.26 parts of 1,4-butanediol; 1.12-1.20 parts of antioxidant; 1.11-1.17 parts of epoxy resin adhesive; and 0.88-0.97 parts of ultraviolet absorber.
[0007] Preferably, the fluorine-containing polyurethane and aliphatic polyurethane elastomer constitute the basic raw materials, the polyvinyl pyrrolidone nanofibers, basalt nanofibers and polyphenylene sulfide nanofibers constitute the fillers, and the glycerol, 1,4-butanediol, antioxidant, epoxy resin adhesive and ultraviolet absorber constitute the additives.
[0008] Preferably, the preparation process of the fluorine-containing polyurethane is:
[0009] S1.1, Raw material selection: perfluoropolyether diol, isophorone diisocyanate, dibutyltin dilaurate and 1,4-butanediol (BDO);
[0010] S1.2, prepolymer synthesis: perfluoropolyether diol and isophorone diisocyanate IPDI are subjected to polymerization reaction under anhydrous conditions, and dibutyltin dilaurate is added to form a prepolymer;
[0011] S1.3, control conditions: control the reaction temperature between 40-45°C, and control the reaction time between 5-5.5h;
[0012] S1.4, introduction of fluorine-containing compounds: adding 1,4-butanediol to further extend the polymer chain, while adjusting the reaction temperature between 55-60°C and the reaction time between 1-1.5h;
[0013] S1.5, Molding: pouring, extruding or calendering the chain-extended polyurethane solution into the desired shape;
[0014] S1.6, curing and cross-linking: Finally, the material is heated to 100-105°C to make the polyurethane undergo a cross-linking reaction, and the fluorine-containing polyurethane is made to improve the strength and durability of the material.
[0015] Preferably, the structure of the aliphatic polyurethane elastomer contains a multiphase structure, distribution of soft and hard segments, and formation of hydrogen bonds.
[0016] Preferably, the manufacturing process of the high wear-resistant polyurethane wheel is manufactured according to the raw materials of the high wear-resistant polyurethane wheel mentioned above, and the manufacturing process flow is:
[0017] Step 1, pretreatment stage: subjecting polyvinyl pyrrolidone nanofibers, basalt nanofibers, and polyphenylene sulfide nanofibers to nanofiber treatment;
[0018] Step 2, material preparation: prepare the formula raw materials by weight of fluorinated polyurethane, aliphatic polyurethane elastomer, polyvinyl pyrrolidone nanofiber, basalt nanofiber, polyphenylene sulfide nanofiber, glycerol, 1,4-butanediol, antioxidant, epoxy resin adhesive and ultraviolet absorber;
[0019] Step 3, mixing stage: preliminarily mixing the fluorinated polyurethane, aliphatic polyurethane elastomer, glycerol, 1,4-butanediol, antioxidant and ultraviolet absorber, and then adding filler to form a mixture;
[0020] Step 4, molding stage: the mixture is subjected to pultrusion molding using a pultruder, and then solidified;
[0021] Step 5, post-processing stage: cutting and grinding are carried out according to the requirements of the manufacturer's design drawings, and finally the finished polyurethane wheel is tested for mechanical properties, durability and weather resistance.
[0022] Preferably, the nanofiber treatment in step 1 is:
[0023] S2.1. Graft polymerization treatment of polyvinyl pyrrolidone nanofibers: glycidyl methacrylate is selected as the monomer solution, benzoyl peroxide of 5 parts by mass is added to form a mixed solution, and the fibers are immersed in the mixed solution to carry out graft polymerization reaction to introduce active functional groups. After the reaction is completed, the fibers are washed with a solvent and dried in a vacuum drying oven at a temperature of 85-90° C. for 30-40 minutes;
[0024] S2.2. Plasma treatment of basalt nanofibers: using low-temperature plasma equipment, setting the power to 100 W and the vacuum degree to 15-20 Pa, exposing the basalt nanofibers to a plasma environment for 5-8 minutes to perform surface modification to improve the bonding strength between the basalt nanofibers and polyurethane. After the modification, the fibers are transferred to an inert gas environment.
[0025] S2.3. Acid wash the polyphenylene sulfide nanofibers: Use a 5% nitric acid solution to soak the fibers in the acid solution for 10-15 minutes while stirring. After soaking, wash the fibers with deionized water for 6-10 times until the pH value is close to 8-9, and place them in a vacuum drying oven and dry them at 60-80°C for 1-1.5 hours.
[0026] Preferably, in step three:
[0027] S3.1. The preliminary mixing process is as follows: mixing the fluorinated polyurethane, aliphatic polyurethane elastomer, glycerol, 1,4-butanediol, antioxidant and ultraviolet absorber at 50-55°C at a speed of 200 r / min for 8-10 minutes, and then ultrasonically treating for 10-12 minutes to obtain a mixture;
[0028] S3.2. The filler adding process is as follows: adding the treated polyvinyl pyrrolidone nanofibers, basalt nanofibers and polyphenylene sulfide nanofibers to the mixture in sequence, and continuing to stir at a speed of 200 r / min for 20-25 min.
[0029] Preferably, the pultrusion process in step 4 is:
[0030] S4.1. Setting the pultrusion machine conditions: The temperature of the pultrusion machine is set at 175℃-180℃;
[0031] S4.2, Feeding and extrusion: Add the mixture into the hopper of the pultruder and extrude the mixture into shape through the extruder head.
[0032] Preferably, in the curing process in step 4, the formed mixture is matured at 20-25° C. for 8-12 hours.
[0033] Preferably, the optimal raw material mass parts of the manufacturing process are: 15 parts of fluorine-containing polyurethane; 19 parts of aliphatic polyurethane elastomer; 8 parts of polyvinyl pyrrolidone nanofibers; 10 parts of basalt nanofibers; 6 parts of polyphenylene sulfide nanofibers; 0.66 parts of glycerol; 0.25 parts of 1,4-butanediol; 1.19 parts of antioxidant; 1.15 parts of epoxy resin adhesive; and 0.89 parts of ultraviolet absorber.
[0034] Compared with the prior art, the present invention provides a highly wear-resistant polyurethane wheel and a manufacturing process thereof, which has the following beneficial effects:
[0035] 1. The present invention controls the mass fraction of raw materials and combines polymer polyurethane with nano-scale reinforcing fibers as raw materials to form a highly cross-linked three-dimensional network structure. The three-dimensional network structure can increase the cohesion of the material, improve the tensile strength and tear resistance, and also enhance the material's resistance to chemical and environmental corrosion, which helps to improve the wear resistance, tear strength and aging resistance of the wheel. BRIEF DESCRIPTION OF THE DRAWINGS
[0036] Figure 1 It is a process flow chart of the present invention. DETAILED DESCRIPTION
[0037] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0038] See also Figure 1 , high wear-resistant polyurethane wheel, the formula of the polyurethane wheel is composed of basic raw materials, fillers and additives. The formula raw materials and their mass parts are: 14-18 parts of fluorine-containing polyurethane; 17-20 parts of aliphatic polyurethane elastomer; 5-8 parts of polyvinyl pyrrolidone nanofiber; 9-11 parts of basalt nanofiber; 4-6 parts of polyphenylene sulfide nanofiber; 0.6-0.7 parts of glycerol; 0.22-0.26 parts of 1,4-butanediol; 1.12-1.20 parts of antioxidant; 1.11-1.17 parts of epoxy resin adhesive; 0.88-0.97 parts of ultraviolet absorber.
[0039] Specifically, the fluorine-containing polyurethane and aliphatic polyurethane elastomer constitute the basic raw materials, the polyvinyl pyrrolidone nanofiber, basalt nanofiber and polyphenylene sulfide nanofiber constitute the filler, and the glycerol, 1,4-butanediol, antioxidant, epoxy resin adhesive and ultraviolet absorber constitute the additive.
[0040] Specifically, the preparation process of fluorinated polyurethane:
[0041] S1.1, Raw material selection: perfluoropolyether diol, isophorone diisocyanate, dibutyltin dilaurate and 1,4-butanediol (BDO);
[0042] S1.2, prepolymer synthesis: perfluoropolyether diol and isophorone diisocyanate IPDI are subjected to polymerization reaction under anhydrous conditions, and dibutyltin dilaurate is added to form a prepolymer;
[0043] S1.3, control conditions: control the reaction temperature between 40-45°C, and control the reaction time between 5-5.5h;
[0044] S1.4, introduction of fluorine-containing compounds: adding 1,4-butanediol to further extend the polymer chain, while adjusting the reaction temperature between 55-60°C and the reaction time between 1-1.5h;
[0045] S1.5, Molding: pouring, extruding or calendering the chain-extended polyurethane solution into the desired shape;
[0046] S1.6, curing and cross-linking: Finally, the material is heated to 100-105°C to make the polyurethane undergo a cross-linking reaction, and the fluorine-containing polyurethane is made to improve the strength and durability of the material.
[0047] Specifically, the structure of aliphatic polyurethane elastomers contains a multiphase structure, a distribution of soft and hard segments, and the formation of hydrogen bonds.
[0048] Specifically, the manufacturing process of the high wear-resistant polyurethane wheel is manufactured according to the raw materials of the high wear-resistant polyurethane wheel mentioned above, and the manufacturing process flow is as follows:
[0049] Step 1, pretreatment stage: subjecting polyvinyl pyrrolidone nanofibers, basalt nanofibers, and polyphenylene sulfide nanofibers to nanofiber treatment;
[0050] Step 2, material preparation: prepare the formula raw materials by weight of fluorinated polyurethane, aliphatic polyurethane elastomer, polyvinyl pyrrolidone nanofiber, basalt nanofiber, polyphenylene sulfide nanofiber, glycerol, 1,4-butanediol, antioxidant, epoxy resin adhesive and ultraviolet absorber;
[0051] Step 3, mixing stage: preliminarily mixing the fluorinated polyurethane, aliphatic polyurethane elastomer, glycerol, 1,4-butanediol, antioxidant and ultraviolet absorber, and then adding filler to form a mixture;
[0052] Step 4, molding stage: the mixture is subjected to pultrusion molding using a pultruder, and then solidified;
[0053] Step 5, post-processing stage: cutting and grinding are carried out according to the requirements of the manufacturer's design drawings, and finally the finished polyurethane wheel is tested for mechanical properties, durability and weather resistance.
[0054] Specifically, the nanofiber treatment in step 1 is:
[0055] S2.1. Graft polymerization treatment of polyvinyl pyrrolidone nanofibers: glycidyl methacrylate is selected as the monomer solution, benzoyl peroxide in a mass fraction of 5 is added to form a mixed solution, and the fibers are then immersed in the mixed solution to carry out graft polymerization reaction to introduce active functional groups. After the reaction is completed, the fibers are washed with a solvent and dried in a vacuum drying oven at a temperature of 85-90° C. for 30-40 minutes to enhance their compatibility with the polyurethane matrix;
[0056] S2.2. Plasma treatment of basalt nanofibers: using low-temperature plasma equipment, setting the power to 100W and the vacuum degree to 15-20Pa, the basalt nanofibers are exposed to a plasma environment for 5-8 minutes for surface modification to improve the bonding between the fibers and polyurethane. After the modification, the fibers are immediately transferred to an inert gas environment to avoid re-adsorption of pollutants in the air and improve the bonding between the fibers and polyurethane.
[0057] S2.3. Acid wash the polyphenylene sulfide nanofibers: Use a 5% nitric acid solution to soak the fibers in the acid solution for 10-15 minutes while stirring to ensure uniform coverage. After soaking, wash the fibers with deionized water 6-10 times until the pH value is close to 8-9, and place them in a vacuum drying oven at 60-80°C for 1-1.5 hours to improve their bonding with polyurethane.
[0058] Specifically, in step three:
[0059] S3.1. The preliminary mixing process is as follows: mixing the fluorinated polyurethane, aliphatic polyurethane elastomer, glycerol, 1,4-butanediol, antioxidant and ultraviolet absorber at 50-55°C at a speed of 200 r / min for 8-10 minutes, and then ultrasonically treating for 10-12 minutes to obtain a mixture;
[0060] S3.2. The filler adding process is as follows: the treated polyvinyl pyrrolidone nanofibers, basalt nanofibers and polyphenylene sulfide nanofibers are added to the mixture in sequence, and stirring is continued at a speed of 200 r / min for 20-25 min to ensure uniform dispersion.
[0061] Specifically, the pultrusion process in step 4 is:
[0062] S4.1. Setting the pultrusion machine conditions: The temperature of the pultrusion machine is set at 175℃-180℃ to allow the material to flow;
[0063] S4.2, Feeding and extrusion: Add the mixture into the hopper of the pultruder so that the pultruder can extrude it, and extrude the mixture into shape through the extruder head.
[0064] Specifically, in step 4, the curing process is as follows: the formed mixture is aged at 20-25° C. for 8-12 hours to ensure that the material is completely cured.
[0065] Example 1
[0066] The formula raw materials of the polyurethane wheel and their mass parts are: 15 parts of fluorine-containing polyurethane; 19 parts of aliphatic polyurethane elastomer; 8 parts of polyvinyl pyrrolidone nanofiber; 10 parts of basalt nanofiber; 6 parts of polyphenylene sulfide nanofiber; 0.66 parts of glycerol; 0.25 parts of 1,4-butanediol; 1.19 parts of antioxidant; 1.15 parts of epoxy resin adhesive; and 0.89 parts of ultraviolet absorber.
[0067] Comparative Example 1
[0068] The formula raw materials of the polyurethane wheel and their mass parts are: 25 parts of fluorine-containing polyurethane; 10 parts of aliphatic polyurethane elastomer; 14 parts of polyvinyl pyrrolidone nanofiber; 10 parts of basalt nanofiber; 9 parts of polyphenylene sulfide nanofiber; 0.66 parts of glycerol; 0.20 parts of 1,4-butanediol; 1.19 parts of antioxidant; 1.15 parts of epoxy resin adhesive; and 0.88 parts of ultraviolet absorber.
[0069] Example 2
[0070] The formula raw materials of the polyurethane wheel and their mass parts are: 16 parts of fluorine-containing polyurethane; 19 parts of aliphatic polyurethane elastomer; 6 parts of polyvinyl pyrrolidone nanofiber; 11 parts of basalt nanofiber; 4 parts of polyphenylene sulfide nanofiber; 0.65 parts of glycerol; 0.22 parts of 1,4-butanediol; 1.15 parts of antioxidant; 1.13 parts of epoxy resin adhesive; and 0.90 parts of ultraviolet absorber.
[0071] Comparative Example 2
[0072] The formula raw materials and their mass parts of the polyurethane wheel are: 16 parts of polyurethane elastomer; 19 parts of polyurethane rubber-coated wheel; 6 parts of polyvinyl pyrrolidone nanofiber; 11 parts of basalt nanofiber; 4 parts of polyphenylene sulfide nanofiber; 0.65 parts of glycerol; 0.22 parts of 1,4-butanediol; 1.15 parts of antioxidant; 1.13 parts of epoxy resin adhesive; and 0.90 parts of ultraviolet absorber.
[0073] Example 3
[0074] The formula raw materials of the polyurethane wheel and their mass parts are: 17 parts of fluorine-containing polyurethane; 18 parts of aliphatic polyurethane elastomer; 7 parts of polyvinyl pyrrolidone nanofiber; 11 parts of basalt nanofiber; 4 parts of polyphenylene sulfide nanofiber; 0.68 parts of glycerol; 0.25 parts of 1,4-butanediol; 1.14 parts of antioxidant; 1.16 parts of epoxy resin adhesive; and 0.96 parts of ultraviolet absorber.
[0075] Comparative Example 3
[0076] The formula raw materials of the polyurethane wheel and their mass parts are: 17 parts of fluorine-containing polyurethane; 18 parts of aliphatic polyurethane elastomer; 7 parts of polyvinyl pyrrolidone fiber; 11 parts of basalt fiber; 4 parts of polyphenylene sulfide fiber; 0.68 parts of glycerol; 0.25 parts of 1,4-butanediol; 1.14 parts of antioxidant; 1.16 parts of epoxy resin adhesive; and 0.96 parts of ultraviolet absorber.
[0077] The polyurethane wheel products of Examples 1-3 and Comparative Examples 1-3 were prepared using the manufacturing process of the present invention, and the mechanical properties, durability, weather resistance and three-dimensional grid tests were performed to obtain the following data tables:
[0078]
[0079]
[0080]
[0081] The following information is obtained through analysis of the above table:
[0082] Mechanical properties: Examples 1, 2, and 3 are superior to corresponding Comparative Examples 1, 2, and 3 in terms of tensile strength and tear strength, showing better mechanical properties.
[0083] Durability: The wear resistance of Examples 1, 2, and 3 is also better than that of their respective comparative examples, indicating that the use of a combination of high molecular weight polyurethane and nano-scale reinforcing fibers to form a highly cross-linked three-dimensional network structure can improve the durability of the product.
[0084] Weather resistance: Compared with comparative examples 1, 2, and 2, embodiments 1, 2, and 3 exhibit longer weather resistance time in the ultraviolet aging test, indicating that they are better than their respective comparative examples in resisting damage from environmental factors.
[0085] Three-dimensional network structure: The three-dimensional network structure of Example 1 (50×50×50 cubic microns), the smaller grid can increase the cohesion of the material, improve the tensile strength and tear resistance, and also enhance the material's resistance to chemical and environmental corrosion.
[0086] (1) Example 1 and Comparative Example 1 were compared with each other using the same raw materials in different mass fractions. The test results of Example 1 were better than those of Comparative Example 1.
[0087] (2) Example 2 was compared with Comparative Example 2, wherein in Comparative Example 2, 16 parts of high molecular weight polyurethane-fluorine-containing polyurethane and 19 parts of aliphatic polyurethane elastomer were replaced with 16 parts of ordinary polyurethane elastomer and 19 parts of polyurethane rubber-coated wheels. The test results of Example 2 were better than those of Comparative Example 2;
[0088] (3) Example 3 is compared with Comparative Example 3. In Comparative Example 3, the nanofibers - 7 parts of polyvinyl pyrrolidone nanofibers, 11 parts of basalt nanofibers and 4 parts of polyphenylene sulfide nanofibers are replaced with 7 parts of ordinary fibers - polyvinyl pyrrolidone fibers, 11 parts of basalt fibers and 4 parts of polyphenylene sulfide fibers. The test results of Example 3 are better than those of Comparative Example 3.
[0089] (4) Finally, Example 1 is compared with Example 2 and Example 3 in terms of the weight percentage of the raw materials in the formula of the present invention, and Example 1 is the best raw material weight percentage after verification and testing.
[0090] From the data analysis of the table, it can be seen that Examples 1, 2, and 3 are superior to Comparative Examples 1, 2, and 3 in terms of mechanical properties, durability, and weather resistance, and Example 1 shows the best performance in all tests, verifying the conclusion that it is the best raw material mass fraction. The above results show that by controlling the mass fraction of raw materials and combining polymer polyurethane with nano-scale reinforcing fibers as raw materials to form a highly cross-linked three-dimensional network structure, it is helpful to improve the wear resistance, tear strength, and aging resistance of the wheel.
[0091] Although embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the invention, and that the scope of the invention is defined by the appended claims and their equivalents.
Claims
1. High wear-resistant polyurethane wheel, characterized in that: The polyurethane wheel is formulated from basic raw materials, fillers and additives, and the raw materials and their weight parts are: 14-18 parts of fluorine-containing polyurethane; 17-20 parts of aliphatic polyurethane elastomer; 5-8 parts of polyvinyl pyrrolidone nanofibers; 9-11 parts of basalt nanofibers; 4-6 parts of polyphenylene sulfide nanofibers; 0.6-0.7 parts of glycerol; 0.22-0.26 parts of 1,4-butanediol; 1.12-1.20 parts of antioxidant; 1.11-1.17 parts of epoxy resin adhesive; and 0.88-0.97 parts of ultraviolet absorber.
2. The highly wear-resistant polyurethane wheel according to claim 1, characterized in that: The fluorine-containing polyurethane and aliphatic polyurethane elastomer constitute basic raw materials, the polyvinyl pyrrolidone nanofiber, basalt nanofiber and polyphenylene sulfide nanofiber constitute fillers, and the glycerol, 1,4-butanediol, antioxidant, epoxy resin adhesive and ultraviolet absorber constitute additives.
3. The highly wear-resistant polyurethane wheel according to claim 1, characterized in that: The preparation process of the fluorinated polyurethane: S1.1, Raw material selection: perfluoropolyether diol, isophorone diisocyanate, dibutyltin dilaurate and 1,4-butanediol (BDO); S1.2, prepolymer synthesis: perfluoropolyether diol and isophorone diisocyanate IPDI are subjected to polymerization reaction under anhydrous conditions, and dibutyltin dilaurate is added to form a prepolymer; S1.3, control conditions: control the reaction temperature between 40-45°C, and control the reaction time between 5-5.5h; S1.4, introduction of fluorine-containing compounds: adding 1,4-butanediol to further extend the polymer chain, while adjusting the reaction temperature between 55-60°C and the reaction time between 1-1.5h; S1.5, Molding: pouring, extruding or calendering the chain-extended polyurethane solution into the desired shape; S1.6, curing and cross-linking: Finally, the material is heated to 100-105°C to make the polyurethane undergo a cross-linking reaction, and the fluorine-containing polyurethane is made to improve the strength and durability of the material.
4. The highly wear-resistant polyurethane wheel according to claim 1, characterized in that: The structure of the aliphatic polyurethane elastomer contains a multiphase structure, the distribution of soft and hard segments, and the formation of hydrogen bonds.
5. The manufacturing process of high wear-resistant polyurethane wheels is characterized in that: The high wear-resistant polyurethane wheel is manufactured from the raw materials of claim 1, and the manufacturing process is as follows: Step 1, pretreatment stage: subjecting polyvinyl pyrrolidone nanofibers, basalt nanofibers, and polyphenylene sulfide nanofibers to nanofiber treatment; Step 2, material preparation: prepare the formula raw materials by weight of fluorinated polyurethane, aliphatic polyurethane elastomer, polyvinyl pyrrolidone nanofiber, basalt nanofiber, polyphenylene sulfide nanofiber, glycerol, 1,4-butanediol, antioxidant, epoxy resin adhesive and ultraviolet absorber; Step 3, mixing stage: preliminarily mixing the fluorinated polyurethane, aliphatic polyurethane elastomer, glycerol, 1,4-butanediol, antioxidant and ultraviolet absorber, and then adding filler to form a mixture; Step 4, molding stage: the mixture is subjected to pultrusion molding using a pultruder, and then solidified; Step 5, post-processing stage: cutting and grinding are carried out according to the requirements of the manufacturer's design drawings, and finally the finished polyurethane wheel is tested for mechanical properties, durability and weather resistance.
6. The manufacturing process of the highly wear-resistant polyurethane wheel according to claim 5, characterized in that: Nanofiber processing in step 1: S2.
1. Graft polymerization treatment of polyvinyl pyrrolidone nanofibers: glycidyl methacrylate is selected as the monomer solution, benzoyl peroxide of 5 parts by mass is added to form a mixed solution, and the fibers are immersed in the mixed solution to carry out graft polymerization reaction to introduce active functional groups. After the reaction is completed, the fibers are washed with a solvent and dried in a vacuum drying oven at a temperature of 85-90° C. for 30-40 minutes; S2.
2. Plasma treatment of basalt nanofibers: using low-temperature plasma equipment, setting the power to 100 W and the vacuum degree to 15-20 Pa, exposing the basalt nanofibers to a plasma environment for 5-8 minutes to perform surface modification to improve the bonding strength between the basalt nanofibers and polyurethane. After the modification, the fibers are transferred to an inert gas environment. S2.
3. Acid wash the polyphenylene sulfide nanofibers: Use a 5% nitric acid solution to soak the fibers in the acid solution for 10-15 minutes while stirring. After soaking, wash the fibers with deionized water for 6-10 times until the pH value is close to 8-9, and place them in a vacuum drying oven and dry them at 60-80°C for 1-1.5 hours.
7. The manufacturing process of the highly wear-resistant polyurethane wheel according to claim 5, characterized in that: In the step three: S3.
1. The preliminary mixing process is as follows: mixing the fluorinated polyurethane, aliphatic polyurethane elastomer, glycerol, 1,4-butanediol, antioxidant and ultraviolet absorber at 50-55°C at a speed of 200 r / min for 8-10 minutes, and then ultrasonically treating for 10-12 minutes to obtain a mixture; S3.
2. The filler adding process is as follows: adding the treated polyvinyl pyrrolidone nanofibers, basalt nanofibers and polyphenylene sulfide nanofibers to the mixture in sequence, and continuing to stir at a speed of 200 r / min for 20-25 min.
8. The manufacturing process of the highly wear-resistant polyurethane wheel according to claim 5, characterized in that: The pultrusion process in step 4: S4.
1. Setting the pultrusion machine conditions: The temperature of the pultrusion machine is set at 175℃-180℃; S4.2, Feeding and extrusion: Add the mixture into the hopper of the pultruder and extrude the mixture into shape through the extruder head.
9. The manufacturing process of the highly wear-resistant polyurethane wheel according to claim 5, characterized in that: The curing process in step 4 is as follows: the formed mixture is cured at 20-25° C. for 8-12 hours.
10. The manufacturing process of the highly wear-resistant polyurethane wheel according to claim 9, characterized in that: The optimal raw materials by weight of the manufacturing process are: 15 parts of fluorine-containing polyurethane; 19 parts of aliphatic polyurethane elastomer; 8 parts of polyvinyl pyrrolidone nanofibers; 10 parts of basalt nanofibers; 6 parts of polyphenylene sulfide nanofibers; 0.66 parts of glycerol; 0.25 parts of 1,4-butanediol; 1.19 parts of antioxidant; 1.15 parts of epoxy resin adhesive; and 0.89 parts of ultraviolet absorber.